Amperometric Detection of Biogenic Amines at the Electrode Modified by Gold Nanoparticles under the Conditions of Flow-Injection Analysis and High Performance Liquid Chromatography - L.G. Shaidarova; I.A. Chelnokova; M.A. Il’ina (Degteva); A.V. Gedmina; H.C. Budnikov (Учёные записки Казанского университета: Серия Естественные науки)
Gold nanoparticles electrodeposited on the glassy carbon electrode show catalytic activity in the electrooxidation of biogenic amines (tyramine, dopamine, epinephrine, and serotonin). Catalysis consists in decreasing of overvoltage of substrate oxidation and in increasing of oxidation current of modifier. The method of amperometric detection of biogenic amines at this modified electrode under the conditions of flow-injection analysis and high performance liquid chromatography has been suggested. The dependence of the analytical signal from the concentration of biogenic amines is linear in the range from 1·10–11 to 2·10–7 mol.